A Scoping Review for Hamstring Injury Risk Monitoring in Australian Rules Football - Dale Wilson Chapman; Sorcha Humphreys; Shannon Spencer; Nathan Tai; Dag Øyen; Kevin Netto; Robert Waller (Encyclopedia, 2025)
Hamstring strain injuries (HSIs) are the most common time loss injury sustained in male Australian Football League (AFL) athletes, causing significant financial cost, time cost, and impaired team and individual performance. In a squad of 42 players, HSIs accounted for 4.86 new injuries sustained by players per club per AFL season in 2020. This is consistent with injury reporting over the last decade in AFL, despite best efforts to reduce the rate. This scoping review sought to firstly identify the reported hamstring injury prevention risk factors in elite AFL, discern the impact of these factors, and map the gaps in the current literature using a biopsychosocial understanding of injury prevention. The scoping review process was based on the Askey and O’Malley framework. Five relevant online databases (MEDLINE, Proquest, CINAHL, SPORTdiscuss, and EMBASE) were systematically searched using a series of Boolean and operator terms following the PRISMA-ScR protocol using the criteria: (1) assessing male professional/elite athletes in AFL; (2) written in English and peer-reviewed; (3) full text available; and (4) published after 2006. Only manuscripts that fit the search terms and inclusion criteria were retained in the scoping review. Following an initial search, 246 potential studies were identified, with 12 studies meeting the inclusion criteria after full-text screening. The risk factors examined were subclassified into modifiable and non-modifiable categories. Modifiable factors include high-speed running exposure, gluteus medius activation, eccentric hamstring strength, shorter bicep femoris fascicle length, use of interchange, and hamstring stiffness. Non-modifiable factors include previous history of HSI and limb injury, age, and size of injury on MRI. This scoping review highlights the need for continued monitoring of high-speed running volumes as rapid increases in completed distances present as a substantial risk factor. The modifiable mechanistic risk factors of eccentric hamstring strength and hamstring stiffness were identified as important components of player screening to reduce the risk of future HSI. Risk factors identified throughout will help develop comprehensive injury profiling for athletes. Further research is warranted to develop a holistic approach to injury profiling.